PROGNOSIS AND RELIABILITY MODELLING FOR HEALTH MONITORING OF INDUSTRIAL GAS TURBINES - AHSAN, SHAZAIB (2019)
Gas turbine engines are highly specialized turbomachines widely used for power generation and direct drive. As compared to other power generation systems, fuel costs and maintenance costs ($4.7/MWh to $5.2/MWh) for gas turbine systems are the most important contributors to the total life cycle cost; hence sustaining high efficiency or healthy behavior through performance or life prediction will have a direct and major effect on the financial performance of these plants.